Takyif fiqhi on the permissibility of ijarah mawsufah fi al-dhimmah: a critical analysis - Ahmad, Abu Umar Faruq; Mohammad Monawer, Abu Talib; Olorogun, Lukman Ayinde (Penerbit Universiti Kebangsaan Malaysia, 2020)
Ijarah mawsufah fi al-dhimmah (hereinafter referred to as IMAD), also known as forward ijarah¸ is an Islamic financial product that involves the sale of an identified asset currently being produced or constructed for a future delivery such as a property, office, factory, and so forth. In the classical fiqh literature, it has been discussed under the general purview of leasing and forward sale contracts. However, in the context of modern Islamic finance practice Islamic banks and financial institutions have upheld its usage as an independent financial instrument. The contemporary scholars claim that except for Hanafi, other key fiqh schools consider IMAD as an Islamic financial product. The study is an attempt to prove that such a claim is merely based on assumption. Besides, it is motivated by lack of holistic study of Hanafi’s original reference books. The methodology chosen for this study is content analysis of the relevant published literatures. The study finds that no classical scholars including those of Hanafi school of thought were in disagreement so far over the IMAD to consider it as an independent and standalone Islamic finance product. The study aims at reconciling scholars’ different views on the issue of IMAD for its wider acceptance.